THE EFFECT OF STOCK PRICE AND TRADE VOLUME OF BID ASK SPREAD IN LQ 45 INDEX PERIOD 2018-2019 - Parulian (STIE Kusuma Negara, 2020)
Analysis of market behavior towards investment decisions in the capital market by looking at the bid ask spread movement. Stock price movements affect the trading volume of shares on the basis of differences in buying and selling prices at a certain time. Trading volume can be seen from the large number of shares traded. This study aims to determine the effect of stock prices and trading volume on the bid ask spread in the LQ 45 index. The population used is all companies incorporated in the LQ 45 index during 2018-2019. The number of samples that meet the requirements of 35 companies. The research method uses panel data with Chow test, Hauman test, t test, F test, and determination with the help of eviwes 10. The results show that stock prices affect the bid ask spread and trading volume does not affect the bid ask spread in the LQ45 index. In other words, this condition is due to variations in trading volume that is not too large during the observation period.